Cadmium-Induced Renal Cell Toxicity Is Associated With MicroRNA Deregulation. (March 2020) - Lemaire, J.; Van der Hauwaert, C.; Savary, G.; Dewaeles, E.; Perrais, M.; Lo Guidice, J. M.; Pottier, N.; Glowacki, F.; Cauffiez, C.
Cadmium is an environmental pollutant well known for its nephrotoxic effects. Nevertheless, mechanisms underlying nephrotoxicity continue to be elucidated. MicroRNAs (miRNAs) have emerged in recent years as modulators of xenobiotic-induced toxicity. In this context, our study aimed at elucidating whether miRNAs are involved in renal proximal tubular toxicity induced by cadmium exposure. We showed that cadmium exposure, in 2 distinct renal proximal tubular cell models (renal proximal tubular epithelial cell [RPTEC]/human telomerase reverse transcriptase [hTERT] and human kidney-2), resulted in cytotoxicity associated with morphological changes, overexpression of renal injury markers, and induction of apoptosis and inflammation processes. Cadmium exposure also resulted in miRNA modulation, including the significant upregulation of 38 miRNAs in RPTEC/hTERT cells. Most of these miRNAs are known to target genes whose coding proteins are involved in oxidative stress, inflammation, and apoptosis, leading to tissue remodeling. In conclusion, this study provides a list of dysregulated miRNAs which may play a role in the pathophysiology of cadmium-induced kidney damages and highlights promising cadmium molecular biomarkers that warrants to be further evaluated.